Taxation, Bonuses, and Tunneling Incentives: Impact on Transfer Pricing Decisions in Manufacturing Companies: Pengaruh Pajak, Mekanisme Bonus, dan Insentif Penyelundupan: Keputusan Penentuan Transfer Pricing pada Perusahaan Manufaktur - Khusnul Khotimah; Santi Rahma Dewi (Academia Open, 2022)
This study examines the empirical relationships between taxation, bonus mechanisms, tunneling incentives, and transfer pricing decisions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2019. Using purposive sampling, data from eleven companies were collected and analyzed through descriptive statistics, normality tests, classical assumption tests, and linear regression. The results reveal that taxes, bonus mechanisms, and tunneling incentives significantly influence transfer pricing decisions in the selected manufacturing companies. This research provides valuable insights for policymakers, regulators, and practitioners in understanding the dynamics of transfer pricing decisions and their implications for manufacturing firms. Highlights: The impact of taxation on transfer pricing decisions: This study investigates the influence of taxes on transfer pricing decisions in manufacturing companies listed on the IDX, providing insights into the relationship between tax policies and transfer pricing strategies. Bonus mechanisms as determinants of transfer pricing decisions: By analyzing the effect of bonus mechanisms on transfer pricing decisions, this research sheds light on the role of incentive structures in shaping the pricing practices of manufacturing companies. Tunneling incentives and transfer pricing decisions: This study explores how tunneling incentives affect transfer pricing decisions, offering valuable insights into the potential risks of opportunistic behavior and their implications for corporate governance and control mechanisms. Keywords: Transfer pricing, taxation, bonus mechanisms, tunneling incentives, manufacturing companies.